Back Cover: Simple and Efficient 1, 3‐Isomerization of Allylic Alcohols using a Supported Monomeric Vanadium‐Oxide Catalyst (ChemCatChem 10/2013). Issue 10 (1st October 2013) - Mitsudome, Takato; Sueoka, Shoichiro; Ikeda, Satoshi; Mizugaki, Tomoo; Jitsukawa, Koichiro; Kaneda, Kiyotomi
<x xml:space="preserve">Abstract</x> Vanadium for victory The cover picture shows that an isolated monomeric vanadium‐oxide species can promote the isomerization of allylic alcohols under liquid‐phase conditions. In their Communication on p. 2879 ff., K. Kaneda et al. present the creation and characterization of the isolated monomeric vanadium species on silica surface (V/SiO2) and the high catalytic activity of V/SiO2 for various allylic alcohols, including under scaled‐up and solvent‐free reaction conditions. This heterogeneous catalyst also exhibits high reusability with no drop in activity. Our results highlight that the monomeric vanadium species plays a crucial role in the isomerization.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>